Online ion-exchange chromatography for small-angle X-ray scattering - Hutin, Stephanie (Acta Crystallogr D Struct Biol, 2016)
Biological small-angle X-ray scattering (BioSAXS) is a powerful technique to determine the solution structure, particle size, shape and surface-to-volume ratio of macromolecules. However, a drawback is that the sample needs to be monodisperse. To ensure this, size-exclusion chromatography (SEC) has been implemented on many BioSAXS beamlines. Here, the integration of ion-exchange chromatography (IEC) using both continuous linear and step gradients on a beamline is described. Background subtraction for continuous gradients by shifting a reference measurement and two different approaches for step gradients, which are based on interpolating between two background measurements, are discussed. The results presented here serve as a proof of principle for online IEC and subsequent data treatment.